If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -2x = 10 + -8 Combine like terms: 10 + -8 = 2 -6 + -2x = 2 Solving -6 + -2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2x = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 2 + 6 -2x = 2 + 6 Combine like terms: 2 + 6 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| .25x+8=.62x+2 | | 15/(8n-32) | | 11x-33=8x+0 | | 2x^2-7x-70=3x | | 5p+2=4p-9 | | (-18)+q=5 | | 2t^2+5=2t^2+1 | | n+n+1+n+1=54 | | 15/8n-32 | | -5.9=k/3 | | 25m^2+2=3 | | 7-3x=5x+14 | | 10x-50=25 | | 3x-6x^2/x^3 | | x*0.65=28748 | | 100-38= | | 2x^2+31-9=0 | | a+2a+3a-b=7a-6 | | 5x-1=15x-72 | | 9(x+12)=18 | | 9=8+z | | 6k+2.3=-9.7 | | 2(2x-4)=3(x+3) | | 5x^2-22=8x | | m+9=4m+12 | | 5n-2=3n+2 | | 1125-5x=960-2x | | 15g+0=24+12g | | -80=9x+10 | | 1/(3x^(2/3)) | | 4(3)-6y=18 | | (2(n-4))/3=5/4 |